Effect of Selenium and Vitamin E on the Level of Sperm HSPA2+, Intracellular Superoxide Anion and Chromatin Integrity in Idiopathic Asthenoteratozoospermia: A Double-Blind, Randomized, Placebo- Controlled Trial - Sabeti , Parvin; Pourmasumi, Soheila; Fagheirelahee , Niloofar (Urology Journal, 2021)
Purpose: Male infertility accounts for about half of all infertility cases. Asthenoteratozoospermia is a severe form of male infertility. Free radicals play an important role in infertility. In a study we found that asthenoteratozoospermic men had a lower mean percentage of sperm HSPA2+ and higher intracellular anion superoxide than normozoospermia. Antioxidants are thought to be able to counteract the negative effects of free radicals. We explored the efficacy of vitamin E in combination with Se on the level of sperm HSPA2+, intracellular anion superoxide and chromatin integrity in these patients. Materials and methods: 60 patients entered the study. They were randomized to treatment group of oral Se (200 μg) in combination with vitamin E (400 units) for 3 months (n= 30) or placebo (n= 30). Semen samples were obtained and assessed for sperm parameters, intracellular O2-, protamine deficiency, sperm HSPA2+ and apoptotic spermatozoa at baseline and after treatment phase. Results: There were no significant differences in baseline semen parameters, intracellular O2- protamine deficiency, sperm HSPA2+ and apoptotic spermatozoa between the treatment and placebo groups. There was a statistically significant decrease in sperm apoptosis and the level of anion superoxide (P=.001) and an increase in sperm motility and viability (P=.001) in the treated group, but no significant difference was found in the percentage of sperm HSPA2+ and sperm protamine deficiency compared with baseline. Moreover, no significant change was found in these parameters in placebo group after 3 months. Conclusion: Our results showed that administration of vitamin E and selenium for three months may improve sperm motility and viability by decreasing intracellular anion superoxide and sperm apoptosis in asthenoteratozoospermic infertile men. We suggest that consuming these supplements before assisted reproductive technology (ART) may improve outcomes in these patients.